Immature stages of Laurotanyus travassosi Oliveira, Messias & Silva-Vasconcelos, 1992 reveal a new synonymy in Tanypodinae (Diptera: Chironomidae) - Dantas, Galileu P.s.; Hamada, Neusa (Zootaxa, 2018)
The monotypic genus Laurotanypus Oliveira, Messias & Silva-Vasconcelos is placed as junior synonym of Procladius Skuse, based mainly on the morphology of immatures. The male of P. travassosi comb. nov. is redescribed and the immature stages are described and illustrated for the first time. In addition, an amendment to the adult male diagnosis of Procladius (Psilotanypus) is provided.